Compressive Assemblies: Bottom‐Up Performance for a New Form of Construction. (July 2017) - Block, Philippe; Rippmann, Matthias; Van Mele, Tom
Abstract : From Inuit igloos to Roman arches to Gothic cathedrals, builders have long used friction and balance to make structures hold together. The Block Research Group at ETH Zurich is involved in ongoing research that investigates historical techniques and fuses them with the latest technologies, including robotics and 3D printing, to establish new methods of architectural assembly. Group founder Philippe Block, co‐director Tom Van Mele and team member Matthias Rippmann explain.